Estimation Of Pelagic Fishing Area in Banten’s Southern Sea - Pratiwi, Andhita Rossi; Irnawati, Ririn; Khalifa, Muta Ali (Agrikan Jurnal Agribisnis Perikanan, 2023)
The purpose of this research are to determine the average distribution of SST, chlorophyll-a, and see surface currents, and analyze the relationship between them with pelagic fish catches as an analysis material for determining pelagic fishing area in Banten’s Southern Sea. Data collected includes SST and chlorophyll-a using Aqua MODIS images data and and see surface currents data from Copernicus Marine Data for 6 years. The data was processed to produce the value of each parameter and then analyzed the parameters with the catches and determine the potential pelagic fishing area. The results showed that the SST throughout 2016 had a relatively high value allegedly due to the negative Indian Ocean Dipole (IOD). During the eastern until the end of second transitional season in 2019 there was a positive IOD which caused SST to decrease and chlorophyll-a to be larger than in other fishing seasons. See surface currents in the western season tend to be larger than in other fishing seasons. SST and chlorophyll-a have a stronger relationship with catches than see surface currents. The potential fishing area are around Tanjung Mantiyung, Muara Binuangeun, dan Tanjung Panto.